RUSSIAN-CHINESE RELATIONS:BETWEEN EUROPE AND THE INDO-PACIFIC. (Part II) Situation Analysis Proceedings - article editorial (Сравнительная политика, 2018)
The Editorial Board of Comparative Politics Russia publishes the second part of the situational analysis which was held in the form of a roundtable to share the results of the analysis of the dynamics and current state of the development of Russian-Chinese relations and the development of the situation in the Asia-Pacific Region. The researchers of the Center for Comprehensive Chinese Studies and Regional Projects of Moscow State Institute of International Relations, the Institute for Far Eastern Studies of the Russian Academy of Sciences, the Institute of Oriental Studies of the Russian Academy of Sciences, the Russian Institute for Strategic Studies, the Institute of Political and Military Analysis, the Institute of Economics of the Russian Academy of Sciences, Primakov Institute of World Economy and International Relations, National Research University Higher School of Economics, National BRICS Committee. Leading Russian experts discussed the current state and prospects of Russian-Chinese relations and the evolution of the situation in the Asia-Pacific region, as well as the formation of a new functional Indo-Pacific region (Indo-Pacific), problems and prospects for new regional projects in Eurasia.